PENGARUH PROGRESSIVE MUSCLE RELAXATION TERHADAP GEJALA FATIGUE PADA KLIEN DIABETES MELITUS TIPE 2 - Antoni, Adi; Dharmajaya, Ridha; Harahap, Ikhsanuddin A (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Progressive Muscle Relaxation (PMR) is a relaxation technique for muscle by tensing or tighteningone certain group of muscles and releasing the tense followed by focusing the mind to feel thesensation of relaxing. This research was aimed at observing the effect of PMR on fatigue symptom ofpeople with Type 2 Diabetes Mellitus (T2DM). Quasi experimental Pretest-Posttest Design withcontrol group was used as the design of this research. The samples were collected by employingconsecutive sampling technique with 66 respondents consisting of 33 people in intervention group andthe other 33 people in control group. The fatigue symptoms observed in this research were measuredby using Piper Fatigue Scale. It was found from the results that there were some significant differenceson the fatigue symptoms before and after giving PMR to both the intervention group with t=43,57,p=<0,001; and the control group with t=1.73, p=0.093. Furthermore, another significant differencewas also found between the intervention and control group which was t= -30.453, and p<0.001.Finally, it was concluded that PMR was effective to reduce the fatigue synptoms of people with T2DM.